Deactivation mechanism of hydrotalcite-derived Ni–AlOx catalysts during low-temperature CO2 methanation via Ni-hydroxide formation and the role of Fe in limiting this effect. Issue 15 (11th July 2019) - Mebrahtu, Chalachew; Perathoner, Siglinda; Giorgianni, Gianfranco; Chen, Shiming; Centi, Gabriele; Krebs, Florian; Palkovits, Regina; Abate, Salvatore
Abstract : Ni–Fe/AlO x with nanosheet structure, enhance the reducibility and stability of the Ni-hydroxide during the catalytic reaction due to the formation of spinel phase which stabilize smaller Ni nanoparticle with a weaker interaction with the support. Abstract : When using undiluted H2 + CO2 feeds in stoichiometric ratios, it is necessary to use a reactor outlet temperature below about 320 °C in CO2 methanation in order to achieve equilibrium conditions which allow the specifications of natural gas to be met. Under these conditions, a deactivation mechanism different from that reported for higher temperature studies is observed in Ni/AlO x catalysts. The water which is formed in situ in the CO2 methanation reaction induces the formation of Ni-hydroxide, which at these low temperatures is not completely reduced to metallic nickel with a consequent decrease of the active phase (metallic Ni), easier sintering and formation of inactive side species. By using a catalyst with a nanosheet structure, prepared from hydrotalcite precursors containing low amounts of Fe, it is possible not only to obtain higher activity and selectivity, but also to enhance the reducibility of Ni-hydroxide during the catalytic reaction, obtaining stable catalysts under extended reaction tests. Under these reaction conditions, no deactivation by coke formation is observed.